The Information of Historical Trade of the Talaud Island Indonesia in International Trade Routes in the Context of the Asean Economic Community - Pratiknjo, Maria Heny; Mambo, Rully (Budapest International Research and Critics University, 2022)
The construction of an economic center in the border region is very important because it is directly adjacent to other countries. Talaud Island Regency is a cluster of archipelagic groups which since the time of BC have experienced a period of glory. At that time even though the trading system was still barter and other traditional trade models. This research is qualitative research, a methods research procedure that produce descriptive data in the form of written or oral words from people and observable behaviors. This arrangement is reflected in the traditional structure of the Talaud archipelago, traditional figures as the pattern of the citizens, being exemplary and highly respected by all citizens of the community, once regulating the social control system in the daily lives of their citizens. This is manifested in various values, attitudes and behavior, among others, in the livelihoods system both as fishermen and farmers in the international trade with traditional models to the context Asean Economic Community (AEC). As a border area, Talaud Island in the North Sulawesi Indonesia can function as: Barriers to separation, seat belts and defenders of state sovereignty, Portrait of identity or image of honor and dignity of the nation and state of the Republic of Indonesia in the interaction of the international community.